3D Mapping of calcite and a demonstration of its relevance to permeability evolution in reactive fractures. (September 2016) - Ellis, Brian R.; Peters, Catherine A.
Highlights: Heterogeneous calcite distribution controls permeability evolution in reactive fractures. Electron microscopy (BSE-EDS) complements X-ray CT to reveal mineral distribution. 3D calcite segmentation maps reactive minerals in natural rock core. Abstract: There is a need to better understand reaction-induced changes in fluid transport in fractured shales, caprocks and reservoirs, especially in the context of emerging energy technologies, including geologic carbon sequestration, unconventional natural gas, and enhanced geothermal systems. We developed a method for 3D calcite mapping in rock specimens. Such information is critical in reactive transport modeling, which relies on information about the locations and accessible surface area of reactive minerals. We focused on calcite because it is a mineral whose dissolution could lead to substantial pathway alteration because of its high solubility, fast reactivity, and abundance in sedimentary rocks. Our approach combines X-ray computed tomography (XCT) and scanning electron microscopy. The method was developed and demonstrated for a fractured limestone core containing about 50% calcite, which was 2.5 cm in diameter and 3.5 cm in length and had been scanned using XCT. The core was subsequently sectioned and energy dispersive X-ray spectroscopy was used to determine elemental signatures for mineral identification and mapping. Back-scattered electron microscopy was used to identify features for co-location. Finally, image analysis resulted in characteristic grayscale intensities of X-ray attenuation that identify calcite. This attenuation mapping ultimately produced a binary segmented 3D image of the spatial distribution of calcite in the entire core. To demonstrate the value of this information, permeability changes were investigated for hypothetical fractures created by eroding calcite from 2D rock surfaces. Fluid flow was simulated using a 2D steady state model. The resulting increases in permeability were profoundly influenced by the degree to which calcite is contiguous along the flow path. If there are bands of less reactive minerals perpendicular to the direction of flow, fracture permeability may be an order of magnitude smaller than when calcite is contiguous. These results emphasize the importance of characterizing spatial distribution of calcite in heterogeneous rocks that also contain a similar abundance of less reactive minerals. Graphical abstract: